Bringing the people back in state building from below in the Nordic countries ca. 1500-1800 - Dørum, Knut 1969-; Hallenberg, Mats 1962-; Katajala, Kimmo 1958- (Routledge research in early modern history, 2021)
Bringing the people back in. Repertoires of state building from below in the Nordic countries, c. 1500-1800 / Knut Dørum, Mats Hallenberg, Kimmo Katajala -- The historical sociology of politics as the study of people, power and agency / Michael Braddick -- The ethics of rule and the pragmatics of resistance: Laurentius Paulinus Gothus and Wilhelm Neumair von Ramsla on good governance and popular politics / Malte Griesse & Miriam Rönnqvist -- Conflict, state formation and literacy / Magne Njåstad -- Statebreaking from below: recognizing the state in wartime rebellions / Sari Nauman -- Pride of the communes: social change in the military organization of sixteenth century Sweden / Martin Neuding Skoog -- Insurgents of the Oldenburg state in Torstensson's War 1643-1645: elements of bargaining, protestation, and independent action / Olli Bäckström -- Households and state-building in early modern Denmark: a disobedient child / Nina Javette Koefoed --